ANALYSIS OF HEAT ABSORBING PLATE ON DRYING RATE AND HEAT USEFUL FOR DRYING ANCHOVY - Mietra Anggara; Pupung Pupung (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
In 2015, Sumbawa Regency produced a total of 736,127 tons of fish catches (Sumbawa Regency Marine and Fisheries Service, 2019). The amount of fish production according to the District in Sumbawa Regency in 2015, which produced the most fish, was in Plampang district with a total of 100,880 tons. This research aims to determine the effect of the shape of the heat-absorbing plate on the drying rate and heat which is useful for anchovies based on LPG gas. The variables used are the shape of the wave plate, triangle and flat and the air blown by the fan from the outside at a speed of 0.5 m/s, 1 m /s and 1.5 m/s. The results obtained in this study are the highest useful heat is 21.25 watts at a speed of 0.5 m/s. While the lowest useful heat is a flat heat absorbing plate, which is 2.83 watts. The best drying rate was found on the corrugated plate which was 1.84 g/minute and the lowest was on the flat plate which was 1.08 g/minute. The water content of dried anchovy was 17.1 % and the most on the flat plate was 80.05%.